Zöld forradalom a szürke zónában : a taylorista mezőgazdaság útvesztői Magyarországon - Schlett, András (Közép-Európai Közlemények, 2012)
This essay examines how Hungarian agriculture tried to use Taylorist labour structure inside the socialist model and what kind of opportunities and barriers this hybrid solution had to face with. This essay tries to touch upon the history of production and logistics. I tried to reconstruct the development of business structure, the change of production technologies, the adaptation of the practical process of production direction. In the centre of the analysis stands the agricultural reconstruction of the sixties and seventies, moreover the eighties when the crisis of the Hungarian agrarian model emerged, and demands for economic and also political reforms could be felt.